The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11434-011-4560-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential release of hydrogen fluoride from domestic coal in endemic fluorosis area in Guizhou, China

Abstract: Almost half of the total rural area of Guizhou Province and many regions within the 11 adjacent provinces in southwestern China have a long history (at least 70 years) of endemic fluorosis, including dental fluorosis and osteofluorosis along with its associated deformities and disabilities. Over decades of research, this specific type of endemic fluorosis has been defined as coal-burning fluorosis, which is distinct from drinking-water fluorosis. It is generally acknowledged that indoor burning and combustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Fluorosis in general, has been identified in various countries (Sinha et al 2000). Almost half of the rural areas of Guizhou province and many regions within the 11 adjacent provinces in southwestern China have a long history (at least 70 years) of endemic fluorosis, including dental fluorosis and osteofluorosis along with its associated deformities and disabilities (Liang et al 2011). Unless effectively controlled, industrial F -emissions, especially from phosphate fertilizer plants and plants producing aluminum, iron, glass, and ceramics, are significant environmental hazard to the biocenosis of water ecosystems (Maria et al 2001).…”
mentioning
confidence: 99%
“…Fluorosis in general, has been identified in various countries (Sinha et al 2000). Almost half of the rural areas of Guizhou province and many regions within the 11 adjacent provinces in southwestern China have a long history (at least 70 years) of endemic fluorosis, including dental fluorosis and osteofluorosis along with its associated deformities and disabilities (Liang et al 2011). Unless effectively controlled, industrial F -emissions, especially from phosphate fertilizer plants and plants producing aluminum, iron, glass, and ceramics, are significant environmental hazard to the biocenosis of water ecosystems (Maria et al 2001).…”
mentioning
confidence: 99%
“…Consequently, developmental defects of the tooth are referred to as coal-burning dental fluorosis [ 4 ]. Extensive investigations have revealed that the fluoride levels of coal used in most places are generally lower than the national average [ 5 , 6 ]. Except for a few regions with high fluoride content in coal, this pathway is not the only contributor to the prevalence of dental defects in China [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using time-of-flight secondary ion mass spectrometry (TOF-SIMS) combined with on-site coal combustion tests, Liang et al [27] verified that naturally outcropping coal, commonly used by locals, was rich in sulfuric acid. This led to the proposition of a new perspective: during usage of coal-fired systems, sulfuric acid facilitates the release of fluorine in the form of hydrogen fluoride (HF), which then pollutes the environment.…”
Section: Introductionmentioning
confidence: 99%